The Relationship between Multiple Intelligences and Biology Learning Outcomes of Student - Rika Andima; Ramadhan Sumarmin; Yuni Ahda; Heffi Alberida; Abdul Razak (Postgraduate, University of Mataram, 2021)
The achievement of learning objectives can be seen from the learning outcomes obtained by students after the learning process. Appropriate learning strategies by paying attention to multiple intelligences in students can affect learning outcomes. This research aims to analyze the relationship of intelligence learning outcomes with the student's biological learning outcomes. This research was conducted on 1st-grade students of natural sciences at Padang High School. The sampling technique is stratified using purposive sampling and proportional random sampling. The research instrument used multiple intelligence questionnaires and multiple-choice questions. The data in this study were analyzed using the Spearman rank correlation test. The results showed that each multiple intelligences had a significant relationship with student learning outcomes, except for three types of intelligence: visual-spatial, physical kinesthetic, and intrapersonal intelligence